2009
DOI: 10.1186/1757-1626-2-74
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell tumor of talus: a case report

Abstract: Giant cell tumor of talus is a rare entity. In contrast to GCT of long bones, most cases occur in a younger age group and tend to be multicentric. The authors report a case of GCT in a 19 year old boy which had led to extensive destruction of the talus. In view of the extensive involvement, total talectomy along with tibio – calcaneal arthrodesis was performed. At 6 months of followup, the patient had a painless and well arthrodesed ankle. There was no evidence of recurrence at 18 months of followup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 3 publications
0
25
0
Order By: Relevance
“…In their case report, Sharma, et al, reported successful treatment of a talar giant cell tumor with talectomy and tibiocalcaneal arthrodesis. 8 The lesion in their case, however, had led to extensive destruction of talus.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In their case report, Sharma, et al, reported successful treatment of a talar giant cell tumor with talectomy and tibiocalcaneal arthrodesis. 8 The lesion in their case, however, had led to extensive destruction of talus.…”
Section: Discussionmentioning
confidence: 90%
“…6 Treatment options include intralesional curettage and bone grafting or talectomy with tibiocalcaneal arthrodesis. 8,13,14 © The Foot and Ankle Online Journal, 2010 Talectomy with tibiocalcaneal arthrodesis is beneficial as it ensures complete removal of the tumor, but it is complicated by limb shortening, disturbed arches of foot and a stiff ankle causing functional limitation. In their case report, Sharma, et al, reported successful treatment of a talar giant cell tumor with talectomy and tibiocalcaneal arthrodesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the fibula distal can be protected less than 3-5 cm., it should be secured with syndesmosis screws. In order to secure ankle stabilization after distal fibula excision, tibiocalcaneal arthrodesis and bond reconstruction with allograft has been recommended (25,26). In one patient, due to fibula distal zone chondrosarcoma, we performed arthrodesis with tibiotalar cross screws.…”
Section: Discussionmentioning
confidence: 99%
“…Limb salvage and amputation is reserved for recurrences only [7]. Radiation therapy is considered for inoperable cases but it has no role in the treatment of completely resected tumours [8].…”
Section: Case Reportmentioning
confidence: 99%